Cost-of-illness study for non-small-cell lung cancer using real-world data - Seung, S.J. (Curr Oncol, 2019)
BACKGROUND: With recent advances in the treatment of non-small-cell lung cancer (nsclc) and current fiscal constraints within publicly funded health care systems, understanding the real-world economic effect of lung cancer management has become important. The objective of the present study was to determine the costs and resources used in the management of nsclc cohorts in Ontario. METHODS: Patients diagnosed between 1 April 2010 and 31 March 2015 were identified in the Ontario Cancer Registry and linked to provincial administrative databases, capturing resources such as hospitalizations, cancer clinic visits, physician services, and systemic therapies or radiotherapy. A cost-of-illness analysis using a bottom-up approach and the GETCOST macro available at ices determined the overall total and mean costs in 2017 Canadian dollars. Resource utilization results were analyzed according to the total number of encounters per resource, the number of patients using each resource, and the number of encounters per patient. A separate cost-and-resource analysis was conducted for radiotherapy. RESULTS: The 24,729 nsclc patients identified included 4542 with stage iii unresectable disease and 10,103 with stage iv nonsquamous disease. The overall total cost for all nsclc patients was $1.9 billion, with inpatient hospitalizations ($635.2 million), cancer clinic visits ($323.7 million), and physician services ($301.4 million) being the top cost contributors. The mean cost per patient was $76,816. The total cost of radiotherapy was $38.5 million. CONCLUSIONS: Real-world costs for the management of nsclc during the 5-year period examined were substantial, despite the fact that median survival was poor and treatment information was limited.